Using free radial forearm flap in the repair of different soft tissue defects in the head and neck region - Zafer Barin, Ensar; Cinal, Hakan (Annals of Medical Research, 2021)
Aim: Radial forearm flap (RFF) is a reliable flap that can be easily used to repair tissue defects in all parts of the body, especially in the areas such as the oral cavity, cheek mucosa and the tongue. It is used for the repair of soft tissue defects as a fasciocutaneous flap, and it is also used as osteo- fasciocutaneous flap, with the radius bone being split into the flap. In this study, we retrospectively examined the cases in which tissue defect repair was performed with free radial forearm flaps in our clinic between the years of 2008and 2018. The purpose of this study; is the determination of the results of the use of the radial forearm flap in the reconstruction of different soft tissue defects belonging to the head and neck region.Material and Methods: RFF repair was conducted in 24 patients who were included in our study. 15 of the patients were male and 9 were female. The mean age of the patients was 49. The cause of tissue defect was tumoral invasion in 17 patients, trauma (traffic accident, fall) in 6 patients and gunshot wound in 1 patient.Results: Total flap loss was observed in 1 patient and partial flap loss was seen in 1 patient. No post-operative infection, bleeding or similar complications were observed. Donor site problems were observed in 4 patients, while the donor area of 2 patients recovered after secondary treatment, while the donor area of the other 2 patients was repaired with additional partial thickness skin grafts.Conclusion: Radial forearm flap with free transfer is an option that has been used safely for many years in many regions, especially in intraoral soft tissue defects such as tongue, inner cheek, and the floor of the mouth. Although harvesting of this flap is slightly easier than other flaps, it is a procedure that requires meticulousness and patience similar to every area where microsurgery exists. Although sacrificing one of the main vessels of the upper limb with this flap is a serious disadvantage, the advantages it offers, especially in the intraoral defects, still keeps the radial forearm flap popular over the years.
Keywords: Free radial forearm flap; head and neck; intraoral soft tissue defects; microsurgery